Improved Diagnostic Accuracy of Breast MRI through Combined Apparent Diffusion Coefficients and Dynamic Contrast-Enhanced Kinetics - Partridge, SC (2011)
This study investigated the relationship between apparent diffusion coefficient (ADC) measures and dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) kinetics in breast lesions, and evaluated the relative diagnostic value of each quantitative parameter. Seventy-seven women with 100 breast lesions (27 malignant and 73 benign) underwent both DCE-MRI and diffusion weighted MRI (DWI). DCE-MRI kinetic parameters included peak initial enhancement, predominant delayed kinetic curve type (persistent, plateau or washout), and worst delayed kinetic curve type (washout>plateau>persistent). Associations between ADC and DCE-MRI kinetic parameters and predictions of malignancy were evaluated. Results showed that ADC was significantly associated with predominant curve type (ADC was higher for lesions exhibiting predominantly persistent enhancement compared to those exhibiting predominantly washout or plateau, p=0.006), but was not significantly associated with peak initial enhancement or worst curve type (p>0.05). Univariate analysis showed significant differences between benign and malignant lesions in both ADC (p<0.001) and worst curve (p =0.003). In multivariate analysis, worst curve type and ADC were significant independent predictors of benign versus malignant outcome and in combination produced the highest area under the ROC curve (AUC = 0.85, AUC=0.78 with 5-fold cross-validation).